A market assessment of additive manufacturing potential for the aerospace industry - (:unkn) unknown (ELSEVIER SCI LTD, 2021)
The additive manufacturing (AM) process, also known as 3D printing, is a process of layer-by-layer material deposition to produce desired parts from 3D model data, as opposed to formative manufacturing methodologies and subtractive manufacturing processes. The AM is one of the most well-suited manufacturing technologies for the aerospace industry where lightweight and unique-shaped components are demanded as this technology produces lightweight and cost-efficient aircraft components with unique geometries. The AM also allows manufacturers to release products with a smaller number of components onto the market; enabling rapid prototyping with less material waste compared to subtractive manufacturing processes. Therefore, during the last two decades, this technology has received research interest and has been adopted by the aerospace industry, resulting in a significant AM market share compared to other sectors. The aerospace industry has been one of the dominant sectors of the global AM market and is forecasted to be one of the leading contributors to the rapidly changing and competitive global AM market. This study reviews the assessment of the recent and forecasted future global aerospace AM market, linked with the historic and forecasted data, and the adoption of this technology, historic and forecasted global aerospace AM market trends, and the impact of Covid-19 pandemic on the current state of the global aerospace sector. Related charts based on historic and forecasted data are given to summarise the global AM market trends and assessment of AM potential for the aerospace industry in this study.
Keywords: Global Aerospace Additive Manufacturing; Market; Additive Manufacturing Market Assessment; Global Aerospace Market Trend; Aerospace Industry; Covid-19 Impact; SUSTAINABILITY; COVID-19; ALLOY